Facile solvothermal syntheses of isostructural lanthanide(III) formates: Photocatalytic, photoluminescent chemosensing properties, and proficient precursors for metal oxide nanoparticles. Issue 9 (25th June 2021) - Farid, Sidra; Ameen, Saima; Sharif, Shahzad; Tariq, Madiha; Kundi, Israr Ahmad; Sahin, Onur; Sayyad, Muhammd Hassan; Khan, Islam Ullah
Abstract: Three isostructural lanthanide coordination polymers (CPs) with the formula C3 H3 LnO6 [Ln = Pr (1 ), Ce (2 ), and Dy (3 )] were solvothermally synthesized by self-assembly of lanthanide(III) and in-situ generated methanoic acid by the hydrolysis of N, N -dimethyl formamide. These CPs were characterized by FTIR, elemental analysis, PXRD, and single crystal analysis. The metal centered luminescence properties of these coordination polymers revealed that only the dysprosium based CP exhibited significant luminescence, and it was found to be selective for chemosensing of picric acid. 3 showed quenching efficiency of 89.7% with KSV value of 2.89 × 10 4 M −1 . These coordination polymers were also exploited as photocatalysts for degradation of methylene blue, and the dysprosium based CP proved to be a fantastic photocatalyst with the degradation activity of 92% owing to its effective electronic transitions. The solvent-free thermolysis of these LnCPs fabricated CeO2 and Pr6 O11 nanoparticles characterized by PXRD, FTIR, particle size analyzer, and elemental analysis. Abstract : UF0001